METHOD OF FORMING OF REPORTS IN NETWORK ARCHITECTURE WITH THREE LEVELS - Краснопольський, А.О.; Косьянчук, О.А. (Proceedings of National Aviation University (archive), 2012)
A research purpose is forming of conception of creation of reports facilities of free fyireporting Software software in network architecture with three levels of access database Microsoft SQL Server on the basis of the real informative system to “Dergatestaciya-K” which is exploited in the National Aviation University. Research object automation of orgware of state attestation of graduating students of educational-qualifying levels “Specialist”, “Magistr” in form qualifying examinations. A research method is based on description of business processes on the basis of application of methodology of Aris and use of diagrams ICD (Information Сarrier Diagram – charts of electrone documents) and to work of mechanism of reports in the system by the method of record select sre-after information in a rdl-file in the XML format. The got results rotined that for such class of the informative systems it is necessary to carry work on creation of windows of these documents from the level of programmer to the level of busin ss-designer by introduction in service of the system of the module of treatment of client messages and base of the windows of information given in relation to forming for reports, which will do necessary selections and form the cuts of information.